Prior secondary cell wall formation is required for gelatinous layer deposition and posture control in gravi‐stimulated aspen. (2nd September 2021) - Takata, Naoki; Tsuyama, Taku; Nagano, Soichiro; Baba, Kei'ichi; Yasuda, Yuko; Sakamoto, Shingo; Mitsuda, Nobutaka; Taniguchi, Toru
SUMMARY: Cell walls, especially secondary cell walls (SCWs), maintain cell shape and reinforce wood, but their structure and shape can be altered in response to gravity. In hardwood trees, tension wood is formed along the upper side of a bending stem and contains wood fiber cells that have a gelatinous layer (G‐layer) inside the SCW. In a previous study, we generated nst/snd quadruple‐knockout aspens ( Populus tremula × Populus tremuloides ), in which SCW formation was impaired in 99% of the wood fiber cells. In the present study, we produced nst/snd triple‐knockout aspens, in which a large number of wood fibers had thinner SCWs than the wild type (WT) and some had no SCW. Because SCW layers are always formed prior to G‐layer deposition, the nst/snd mutants raise interesting questions of whether the mutants can form G‐layers without SCW and whether they can control their postures in response to changes in gravitational direction. The nst/snd mutants and the WT plants showed growth eccentricity and vessel frequency reduction when grown on an incline, but the triple mutants recovered their upright growth only slightly, and the quadruple mutants were unable to maintain their postures. The mutants clearly showed that the G‐layers were formed in SCW‐containing wood fibers but not in those lacking the SCW. Our results indicate that SCWs are essential for G‐layer formation and posture control. Furthermore, each wood fiber cell may be able to recognize its cell wall developmental stage to initiate the formation of the G‐layer as a response to gravistimulation. Significance Statement: Secondary cell walls are required in the xylem fibers of aspens ( Populus tremula × Populus tremuloides ) to ensure the appropriate response to gravistimulation.